Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Loyalitas Karyawan dengan Kepuasan Kerja Karyawan sebagai Variabel Intervening - Urmila, Salwa; Rayuwanto, Rayuwanto (Keizai, 2022)
This study aims to find out the impact of work environment and work stress on employee loyalty with employee job satisfaction as an intervening variable. The population is all employees who work at UD.Tiga Sewarga totaling 37 people. The sampling method used is a saturated sample with the research instrument in the form of a Likert scale questionnaire. The data analysis method used is multiple linear regression and path analysis. The results showed that the work environment did not have a significant impact on employee job satisfaction with the coefficient value. 0.069, job stress has a significant impact on employee job satisfaction with a coefficient value. 0.483, the work environment does not have a significant impact on employee loyalty with a coefficient value. 0.328, work stress has no significant impact on employee loyalty with a coefficient value. -0.020, employee job satisfaction has a significant impact on employee loyalty with a coefficient value of 0.638.